Adapting the World Health Organization’s Surgical Safety Checklist to High-Income Settings: A Hybrid Effectiveness-Implementation Trial Protocol - Nathan Turley, MA, MBA; Karolina Kogut, BA; Barbara Burian, PhD; Rachel Moyal-Smith, DrPH, PA-C; James Etheridge, MD, MPH; Yves Sonnay, MScPH; William Berry, MD, MPH; Alan Merry, MD, MBChB; Alexander Hannenberg, MD; Alex B. Haynes, MD, MPH; Roger D. Dias, MD, PhD, MBA; Kathryn Hagen, MD; et al. (Annals of Surgery Open)
Objectives:. The proposed study aims to assess users’ perceptions of a surgical safety checklist (SSC) reimplementation toolkit and its impact on SSC attitudes and operating room (OR) culture, meaningful checklist use, measures of surgical safety, and OR efficiency at 3 different hospital sites. Background:. The High-Performance Checklist toolkit (toolkit) assists surgical teams in modifying and implementing or reimplementing the World Health Organization’s SSC. Through the explore, prepare, implement, and sustain implementation framework, the toolkit provides a process and set of tools to facilitate surgical teams’ modification, implementation, training on, and evaluation of the SSC. Methods:. A pre–post intervention design will be used to assess the impact of the modified SSC on surgical processes, team culture, patient experience, and safety. This mixed-methods study includes quantitative and qualitative data derived from surveys, semi-structured interviews, patient focus groups, and SSC performance observations. Additionally, patient outcome and OR efficiency data will be collected from the study sites’ health surveillance systems. Data analysis:. Statistical data will be analyzed using Statistical Product and Service Solutions, while qualitative data will be analyzed thematically using NVivo. Furthermore, interview data will be analyzed using the Consolidated Framework for Implementation Research and reach, effectiveness, adoption, implementation, maintenance implementation frameworks. Setting:. The toolkit will be introduced at 3 diverse surgical sites in Alberta, Canada: an urban hospital, university hospital, and small regional hospital. Anticipated impact:. We anticipate the results of this study will optimize SSC usage at the participating surgical sites, help shape and refine the toolkit, and improve its usability and application at future sites.